An attempt to explore components of empathic architecture in hospitals – a study of Indian hospitals. Issue 1 (2nd January 2016) - Banerji, Haimanti
Abstract: Patients coming to the hospital are often fearful and confused and these feelings may impede recovery. Purpose of this study is to find out how the hospital stay can be made unthreatening, comfortable, and stress-free as possible by preserving, restoring and creating a preferred environment. An exhaustive study has been conducted with a well designed questionnaire along with photography and behaviour mapping in three hospitals in Eastern India. A list of fourteen environmental attributes associated with creation of a healing environment within hospital set up was prepared. The perception of psychological comfort associated with these attributes was measured using a five – point scale. For futher analysis, the researcher adopted Principal Component Analysis Technique and Varimax Factor Rotation Technique to extract major factors of hospital design with empathy. The findings of this research reassures the fact that no longer should the ethics of healthcare be viewed exclusively through the lens of physician-patient dyad but architects associated with hospital design bear equal responsibilities. The analyses have successfully highlighted issues like psycho – physical vulnerability of patients and family stress associated with hospitalization. The research concludes by suggesting some architectural design principles, which are helpful in generating a sense of trust, and faith on the hospital set up, familiarizing the patients and their relatives with hospital working system and process of treatment andcreating a non – clinical overall appearance. It also highlights the need for comforting the patients through various rejuvenating elements and helping them in negating the fear of unknown through information dissipation and counselling.